Globalne testy szkolne i ukryty program neoliberalnej kolonizacji - Gromkowska-Melosik, Agnieszka (Studia Edukacyjne, 2020)
Tests have influence on the phenomenon of stratification and selection of students, their lifestyle and way of thinking. Without a doubt, they have their hidden curriculum. At the micro level tests shape the identity of the individual. They are a factor of socialization. On the other hand, at the macro level tests are the significant instrument of educational policy governments. In my article I analyse the second problem – in the context of international developments PISA tests, which are an instrument of neo-liberal policies of national governments, as well as the OECD. The tests are part of the abandonment of the idea of "equality in education" for the system market and competitiveness, in which education ceases to be a "public good" and becomes a "personal good." The essence of the hidden curriculum PISA test is the pursuit of homogenization student population living in culturally different countries as well as the shaping the attitudes of rivalry.